Desempenho ambiental : melhorias considerando a aplicação integrada das normas ISO 14001 e ISO 50001 - Nascimento, Naiana Moraes do (2021)
The large increase in greenhouse gas emissions since the beginning of the industrial era has had a considerable impact on human systems on all continents of the world. As a result, agreements between nations have been signed and international standards can be used as tools to help implement the 2020 Agenda for sustainable development. Thus, the ISO 14001 standard proposes an environmental management system and a framework to improve the environmental performance of all environmental aspects and impacts of an organization. Therefore, the ISO 50001 defines the requirements of an energy management system, working on a method of continuous improvement of only one environmental aspect and impact, but one of the most relevant today, which is energy use and consumption. Then, the objective of this work was to discuss the improvements in environmental performance that the integrated application of the ISO 14001:2015 and the ISO 50001:2018 management systems can generate in an organization. To achieve that, the methodology adopted was an extensive literature review to create two hypotheses that gave rise to a questionnaire and then the application of a survey-type research in ISO 14001-certified organizations located in the Southeast region of Brazil.Lastly , the data collected were analyzed and discussed. Even so, the data reflects the hypothesis that the ISO 14001 methodology has many opportunities for improvement that can be taken as a lesson from ISO 50001 and, thus, leverage environmental performance results in organizations. It was found that the energy management methodology proposed in ISO 50001 contains more specific steps aimed at data collection and analysis, definition of indicators and goals, and a baseline to compare the organization's energy performance in relation to its initial state, aiming at continuous improvement of energy performance, in addition to other practices, such as energy review and the project phase for improvements that will only be effective through investments. It was concluded that the data reflected the hypothesis that the ISO 14001 methodology has many opportunities for improvement that can be taken as a lesson from ISO 50001 and, thus, leverage the results of environmental performance in organizations. Based on the responses of ISO 50001 certified organizations, it can be concluded that adopting the standard not only benefited the organization's energy performance results, but also its environmental performance. Finally, it is believed that the work may be useful for ISO technical committees and groups that discuss the creation of management system standards, opening space for provocations in the structuring of standards. It may also be beneficial for organizations that adopt ISO 140001 and ISO 50001 standards in their processes, enabling these organizations to identify best practices based on the integration of these standards